Synthesis of novel bismaleimide monomers based on fluorene cardo moiety and ester bond: Characterization and thermal properties. Issue 2 (1st February 2016) - Zhang, Liying; Chen, Ping; Na, Liyan; Gao, Mingbo; Jin, Liming; Fan, Shengdi
ABSTRACT: Two novel bismaleimide monomers based on fluorene cardo moiety and ester bonds, namely 9, 9-bis[4-(4-maleimidobenzoate) phenyl]fluorene (PEFBMI) and 9, 9-bis[4-(4-maleimidobenzoate)-3-methylphenyl]fluorene (MEFBMI) were designed and synthesized. Their structures were confirmed by FTIR, 1 H-NMR, 13 C-NMR spectroscopy and Elemental analysis. Both monomers obtained have excellent solubility in some organic solvents with low boiling point, including acetone, chloroform and dichloromethane. The curing process of the monomers were investigated by DSC, displaying that the melting point of the monomers were 157.1°C and 193.6°C respectively, and all processing windows exceed 30°C. DMA results showed the glass transition temperature of the cured PEFBMI/glass cloth composite was higher than 390°C while that of the cured PEFBMI composite was 349.2°C. TGA results indicated that the cured BMI resins have good thermal stability and their 5% weight loss temperatures were both higher than 410°C.